KELURAHAN SILALAS SEBAGAI INNOVATION HUB: STRATEGI KOMPETITIF PEMERINTAH KOTA MEDAN MELALUI PERANGKAT KEWILAYAHANNYA (SILALAS SUBDISTRICT AS INNOVATION HUB: THE COMPETITIVE STRATEGY OF CITY GOVERNMENT OF MEDAN THROUGH ITS TERRITORIAL ORGANIZATIONS) - Herie Saksono (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
The problematic of public services in urban areas originates from subdistrict/village as the leading governmental administrative entity. Silalas Subdistrict is one of the subdistricts in Medan Barat District, which is the main door for subdistrict community to get excellent service, ultima and optima in their area. In an effort to build a conducive climate that has competitiveness, breakthrough and innovation are needed. What strategy did the Medan City Government, West Medan District Head (Camat), Silalas Subdistrict Head (Lurah), and Silalas Subdistrict Officers? This study is an evaluative research with qualitative-descriptive method. The results of the analysis prove that the existence of the subdistrict is very strategic in the perspective of public service. Acceleration of community welfare achievement in subdistricts is determined by the existence and ability to manage territorial capital and human capital as well as social interaction through cooperation and collaboration in innovation-hub. It is hoped that the presence of innovation-hub will open access to services, unify public perceptions of the importance of innovation for prosperity, and stimulating community participation in every development/empowerment activity. In addition, it can increase the public acceptability of successful development initiated and carried out in togetherness between the mayor, district head (Camat), sub-district head (Lurah), sub-district apparatus, and community members. This study recommends that Silalas Sub-district can be an example/role model and role model for other sub-districts in Medan. Keywords:Innovation-hub, Evaluation, Silalas Subdistrict, Competitiveness Strategy, and Medan City.